MEDIA LITERASI AL-QUR’AN BAGI PENYANDANG DISABILITAS SENSORIK RUNGU WICARA - Ahmad Jaeni; Muchlis Muhammad Hanafi; Ali Akbar; Imam Arif Purnawan; Jonni Syatri; Irwan Irwan; Harits Fadlly; Dwi Martiningsih (Lajnah Pentashihan Mushaf Al-Qur'an, 2021)
This paper presents the results of research on the Qur’anic literacy media for the persons with deaf sensory disabilities in reading the Qur’an. This research is important to do, considering that there is no standard of the Qur’anic literacy media yet that can be used according to the conditions and needs of for the persons with deaf sensory disabilities. As a result, the persons with deaf sensory disabilities’ access to the Qur’an is still low, because learning activities are still very limited to certain communities or institutions. This exploratory research seeks to uncover and map the literacy media being used in 12 Qur’anic learning centers for persons with deaf sensory disabilities. Based on the results of data analysis, it was found that there were two types of the Qur’anic literacy media, namely oral-based and sign-based. Oral-based literacy media are basically used as literacy media for hearing people, and are generally used for children whose oral potential can still be developed. Meanwhile, gesture-based media also takes two main models, gesture based on reading (recitations), and gesture based on writing (kitabah).